1997
DOI: 10.1038/sj.bmt.1700901
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy followed by autologous blood cell transplantation: a safe and effective outpatient approach

Abstract: led us to investigate the feasibility of early discharge and outpatient follow-up. High-dose chemotherapy (HDCT) followed by autologous blood cell (ABC) transplantation has been used Accordingly, a three-step approach was planned and executed. The results of this study are reported here. widely for patients with metastatic breast cancer (MBC). It has been shown by our group and others to be an effective means of achieving very high response rates including complete remission. Therefore, furtherPatients and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Since the early 1990s, there have been several published reports of successful outpatient-based autologous HSCT. [7][8][9][10][11][12][13][14][15] The experience with outpatient management of allogeneic HSCT has been quite limited outside the context of nonmyeloablative HSCT. [16][17][18] The group at John Hopkins reported on an in-patient-outpatient continuumof-care model for both autologous and allogeneic HSCT that resulted in a substantial cost savings, particularly in patients with standard risk disease, without an increase in clinical complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 1990s, there have been several published reports of successful outpatient-based autologous HSCT. [7][8][9][10][11][12][13][14][15] The experience with outpatient management of allogeneic HSCT has been quite limited outside the context of nonmyeloablative HSCT. [16][17][18] The group at John Hopkins reported on an in-patient-outpatient continuumof-care model for both autologous and allogeneic HSCT that resulted in a substantial cost savings, particularly in patients with standard risk disease, without an increase in clinical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that autologous HSCT can be safely delivered in the outpatient setting with good outcomes and diminished cost. [7][8][9][10][11][12][13][14][15] In addition, allogeneic transplantation after nonmyeloablative conditioning also seems feasible in the ambulatory care setting, [16][17][18] given its significantly reduced regimen-related toxicities compared with standard allogeneic HSCT. A few pilot studies have explored the safety of outpatient myeloablative allogeneic HSCT 4,19 in small numbers of selected patients, but none have documented whether this approach is generalizable to the majority of patients requiring such therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A growing number of studies showing the feasibility, safety and cost reduction of OP auto-HSCT in patients with hematological malignancies have led to an increased acceptance of this approach. [5][6][7][8] However, extension of this model into the allogeneic (allo)-HSCT transplant population has not occurred. An early publication by Russell et al 9 described 50 consecutive patients receiving an allo-HSCT, nursed in a single room that included a subset of patients who were allowed to go home during their neutropenic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, a number of studies have investigated the efficacy, safety and cost advantages of reduced hospitalization for auto-SCT. [5][6][7][8][9][10][11][12][13][14][15][16][17] During this time several models of outpatient (home-and clinic-based or daily clinic-based) and early discharge care (with or without planned readmission) have emerged. 18 Studies usually conclude that HDCT is feasible and safe in the outpatient setting, thanks to the use of hematopoietic growth factors and antimicrobial prophylaxis, which lower aplasia related complications.…”
Section: Introductionmentioning
confidence: 99%